An econometric analysis of charitable donations in the Republic of Ireland - Carroll, James; McCarthy, Siobhan; Newman, Carol (Economic & Social Studies, 2005)
This paper explores the variables that affect the probability of donating to charity and those that affect the size of donations by Irish households. The dataset employed is the Irish Household Budget Survey (HBS) 1999/2000, which is analysed using a tobit model and double-hurdle model with an inverse hyperbolic sine transformation of the dependent variable. To date,there has been no prior econometric analysis of charitable donations in the Republic of Ireland.
Paper presented at the Nineteenth Annual Conference of the Irish Economic Association, Kilkenny, 2005
Keywords: Charitable donations; Econometric analysis; Ireland